2022
DOI: 10.3390/d14010044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genetic Diversity among Weedy Rice Accessions Differing in Herbicide Tolerance and Allelopathic Potential

Abstract: Increasing agricultural productivity is indispensable to meet future food demand. Crop improvement programs rely heavily on genetic diversity. The success of weeds in the ecosystem can be attributed to genetic diversity and plasticity. Weedy rice, a major weed of rice, has diverse morphology and phenology, implying wide genetic diversity. Study was conducted to genotype weedy rice accessions (n = 54) previously phenotyped for herbicide tolerance and allelopathic potential using 30 SSR markers. Cultivated rice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In Sungai Leman, Selangor, Shannon’s information index was zero for all three diseases ( Table 6 ). This could be because only eight samples (N = 8) were collected from this particular location, and the limited sample size might not accurately reflect the genetic diversity of the population [ 53 ]. We recommend that weedy population genetics studies use larger sample sizes to better capture the genetic diversity of populations in a specific location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sungai Leman, Selangor, Shannon’s information index was zero for all three diseases ( Table 6 ). This could be because only eight samples (N = 8) were collected from this particular location, and the limited sample size might not accurately reflect the genetic diversity of the population [ 53 ]. We recommend that weedy population genetics studies use larger sample sizes to better capture the genetic diversity of populations in a specific location.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that 89% of the tested weedy biotypes were resistant to bacterial leaf blight, indicating the potential to introduce resistance alleles from local weedy biotypes into cultivated rice varieties that are susceptible to the disease. Given that rice and weedy rice are closely related and have a low breeding barrier [ 53 ], we urge that the potential and genetic diversity of weedy rice be explored further for use in rice breeding programs.…”
Section: Discussionmentioning
confidence: 99%